Spin–lattice relaxation phenomena in the magnetic state of a suggested Weyl semimetal CeAlGe. Issue 13 (2nd July 2020) - Singh, Karan; Mukherjee, K.
ABSTRACT: In this work, we report the results of DC susceptibility, AC susceptibility and related technique, resistivity, transverse and longitudinal magnetoresistance and heat capacity on polycrystalline magnetic semimetal CeAlGe. This compound undergoes antiferromagnetic type ordering around 5.2 K ( T 1 ). Under the application of external magnetic fields, parallel alignment of magnetic moments is favoured above 0.5 T. At low field and temperature, frequency and AC field amplitude response of AC susceptibility indicate the presence of spin–lattice relaxation phenomena. The observation of spin–lattice interaction suggests the presence of the Rashba–Dresselhaus spin–orbit interaction which is associated with inversion and time-reversal symmetry breaking. Additionally, the presence of negative and asymmetric longitudinal magnetoresistance indicates anomalous velocity contribution to the magnetoresistance due to the Rashba–Dresselhaus spin–orbit interaction which is further studied by heat capacity.